The pH of the Host Niche Controls Gene Expression in and Virulence of Candida albicans - De Bernardis, Flavia (American Society for Microbiology, 1998)
Little is known of the biological attributes conferring pathogenicity on the opportunistic fungal pathogen Candida albicans. Infection by this pathogen, as for bacterial pathogens, may rely upon environmental signals within the host niche to regulate the expression of virulence determinants. To determine if C. albicans responds to the pH of the host niche, we tested the virulence of strains with mutations in either of two pH-regulated genes, PHR1 and PHR2. In vitro, PHR1 is expressed when the ambient pH is at 5.5 or higher and deletion of the gene results in growth and morphological defects at neutral to alkaline pHs. Conversely, PHR2 is expressed at an ambient pH below 5.5, and the growth and morphology of the null mutant is compromised below this pH. A PHR1 null mutant was avirulent in a mouse model of systemic infection but uncompromised in its ability to cause vaginal infection in rats. Since systemic pH is near neutrality and vaginal pH is around 4.5, the virulence phenotype paralleled the pH dependence of the in vitro phenotypes. The virulence phenotype of a PHR2 null mutant was the inverse. The mutant was virulent in a systemic-infection model but avirulent in a vaginal-infection model. Heterozygous mutants exhibited partial reductions in their pathogenic potential, suggesting a gene dosage effect. Unexpectedly, deletion of PHR2 did not prevent hyphal development in vaginal tissue, suggesting that it is not essential for hyphal development in this host niche. The results suggest that the pH of the infection site regulates the expression of genes essential to survival within that niche. This implies that the study of environmentally regulated genes may provide a rationale for understanding the pathobiology of C. albicans.